Resenha: ANTUNES, António Lobo. Eu hei-de amar uma pedra. Lisboa: Dom Quixote, 2004. (Revista do Centro de Estudos Portugueses, 2005)
Resenha: ANTUNES, António Lobo. Eu hei-de amar uma pedra. Lisboa: Dom Quixote, 2004.